Embryo transfer of dorper breed to Mongolian sheep - Chuluunbayar Uuganbayar; Tsolmonbaatar Boldsaikhan; Byambasaikhan Danzan-Osor; Ho-Jun Lee; Sang-Hwan Kim; Enkhbolor Barsuren (The Korean Society of Animal Reproduction and Biotechnology, 2022)
The sheep can be reproduced by natural mating as well as applied reproductive biotechnology, embryo transfer (ET). However, this method in sheep is influenced by several factors such as season, photoperiod, latitude, temperature, nutrition, and breed. In addition, there is still less research on assisted reproductive technologies in small ruminants, compared to other livestock species such as cattle and pigs. Because there has been a need for an optimization and a continuous improvement of ET techniques in small ruminants. the main objective of this study was to evaluate the conception rate obtained after ET in Mongolian sheep (Dorper breed). After embryo recover, code 1 and 2 embryos (morula or blastocyst stage) for ET in the present study were 63% (63/100) and 24% (24/100), respectively. Then Each single embryo was transferred to a synchronized recipient who prepared by estrous synchronization protocol with fluorogestone acetate-cloprostenol sodium. The results demonstrated that an average conception rate and lambing rate was 35.6% (31/87) and 33.3% (29/87), respectively. Further study is still necessary, but these results indicated that single embryo of Mongolian sheep with the present protocol was enough to conducting ET when the genetically superior sheep were necessary to be expanded.